Keratosis rubra pilaris/Atopic dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
(...) Keratosis rubra pilaris must be differentiated from atopic dermatitis. The intense erythema with sudden worsening, the early onset, the long duration are reminiscent of atopic dermatitis, which is a much more frequent disease. The differential diagnosis is based upon an anamnestic criterion and some clinical features. (...).